Taqwīm taʿlīm al-lughah al-ʿArabiyyah fī al-faṣl al-tāsiʿ bi-Maʿhad Situwangi Garut fī ḍawʾ namūdhaj al-siyāq wa-al-madkhalāt wa-al-ʿamaliyyah wa-al-muntaj (CIPP) - Muhtar, Abdul Fatah; Bahruddin , Uril; Chamidah, Dewi (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2023)
The problems of teaching Arabic at Situwangi Boarding School are the small number of specialized Arabic language teachers, the Arabic language teaching class is few, and the lack of continuous evaluation. And that the evaluation has a major role in knowing the extent to which the goals and decision-making are achieved for the Arabic language learning program, and context, input, process and product evaluation model is used because it is more comprehensive than other evaluation models. The objectives that the researcher wants to reach by writing this research are to describe the reality of teaching the Arabic language at the Situwangi Boarding School, its inputs, implementation and results. In this research, the researcher uses the qualitative approach and the method of descriptive and evaluation study. The method used by the researcher to obtain the desired data are: interview, observation, documents, and questionnaire. The results of the research are that teaching Arabic at the Situwangi Boarding School according to the (CIPP) model in terms of reality in terms of the result is inappropriate so that the component of "achieving the objectives" and "desired result" is not appropriate by the criterion and the component of "used expense" is not appropriate to the standards. In conclusion, the Arabiyah BayinaYadaik is a distinguished book, but you need a teacher who specializes and knows the process of teaching it well.